Diseño y construcción de un elevador desmontable electro-hidráulico tipo desplegable para un camión de 3 ejes para elevar carga hasta 500kg - Quintana Sucuzhañay, Gonzalo Javier (2018)
The project was elaborated in three chapters in which theory, design and cost analysis were developed, the objective was to implement an electro-hydraulic elevator for loading up to 500kg, with the purpose of eliminating to a great extent the manual process of loading and truck unloading, the implementation was made in the truck of the company INSEIN. INC. LTDA Located in the northern sector of the city of Quito. For the implementation, the loading and unloading process of the truck was analyzed, and three alternatives of elevators were proposed, considering variables such as design, functionality, weight and cost. The ergonomic and economic impact is considerable, the loading and unloading process is now carried out by a single person who is in charge of operating the electro-hydraulic elevator, the physical impact and the excess of personnel required during the process were reduced. An analysis of three alternatives of elevators in which technical information related to the load capacity, design of the structure, electrical and hydraulic components, structural weight, manufacturing cost, manufacturing time and ergonomics, was selected. option as the most feasible for implementation. The elevator that meets the needs of the company was selected. Once the elevator was selected, the structural design process was started, in which types of profiles, materials, thicknesses, pins, plates, hydraulic system and accessories were selected. The hydraulic components were selected respecting the design parameters. The cost analysis was developed to determine the recovery time of the investment based on the reduction of preserves per man hours and the number of personnel required.